Potential Novel Risk Factor for Breast Cancer: Toxocara canis Infection Increases Tumor Size Due to Modulation of the Tumor Immune Microenvironment - Ruiz-Manzano, Rocío Alejandra; Palacios-Arreola, Margarita Isabel; Hernández-Cervantes, Rosalía; Del Río-Araiza, Víctor Hugo; Nava-Castro, Karen Elizabeth; Ostoa-Saloma, Pedro; Muñoz-Cruz, Samira; Morales-Montor, Jorge (Frontiers in Oncology, 2020)
Worldwide breast cancer is the most important type in regard to incidence and prevalence in women. Several risk factors interact to increase the probability of breast cancer development. Biological environmental contaminants such as infectious agents play a significant role in tumor development, and helminths have been recognized as cancer enhancers or inducers due to their ability to regulate the host immune response. However, nothing it is not known in regard to parasites and breast cancer. Toxocara canis is a zoonotic and cosmopolite nematode, with immuno-regulatory abilities. T. canis infection has been related to T helper type-2 cell (Th2 or type 2) and regulatory responses. Type 2 and regulatory immune responses may favor the development of comorbidities that are usually controlled or eliminated through a type 1 response, such as cancer. The aim of this study was to determine if T. canis infection alters mammary tumor growth through modulation of the immune response. Infected mice developed larger tumors. Tumor immune cell milieu analysis revealed that infection reduced CD8+ T lymphocytes, and increased F4/80+ macrophages as well as CD19+ B cells proportions. These changes were accompanied by a type 2 local response represented by increased amounts of IL-4, VEGF, and a regulatory microenvironment associated with higher IL-10 levels. Thus, this study demonstrates that T. canis infection enhances tumor development and suggests that this is through the modulation of tumor immune microenvironment.